THE PLACE AND SIGNIFICANCE OF LEGAL EDUCATION IN THEFORMATION OF LEGAL AWARENESS OF STUDENT YOUTH (Universal International Scientific Journal, 2026)
This article reveals the role of legal education in the formation of legal awareness and legalculture in the minds of the younger generation. It analyzes effective methods and tools for theformation of students' respect for laws, legal responsibility, civic activity. In addition, theimportance of educating a strong legal consciousness and cultured generation serving to build alegal state and civil society through the proper organization of legal education in the educationalprocess is substantiated.
Keywords: legal awareness; legal culture; legal education